Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

if h(x) = x-7 and g(x)

Sagot :

Answer:

If you would like to find the equivalent expression to (g*h)(5), you can do this using the following steps:

h(x) = x - 7

g(x) = x^2

(g*h)(x) = g(h(x)) = g(x - 7) = (x - 7)^2

(g*h)(5) = g(h(5)) = g(5 - 7) = (5 - 7)^2 = (-2)^2 = 4

The correct result would be (5 - 7)^2.

Step-by-step explanation: